Cosmology and the Scientific Self in the Nineteenth Century - Carlton, Howard. author. aut Link
XII, 315 p.
Keywords: This book argues that while the historiography of the development of scientific ideas has for some time acknowledged the important influences of socio-cultural and material contexts, the significant impact of traumatic events, life threatening illnesses and other psychotropic stimuli on the development of scientific thought may not have been fully recognised. Howard Carlton examines the available primary sources which provide insight into the lives of a number of nineteenth-century astronomers, theologians and physicists to study the complex interactions within their ‘biocultural’ brain-body systems which drove parallel changes of perspective in theology, metaphysics, and cosmology. In doing so, he also explores three topics of great scientific interest during this period: the question of the possible existence of life on other planets; the deployment of the nebular hypothesis as a theory of cosmogony; and the religiously charged debates about the ages of the earth and sun. From this body of evidence we gain a greater understanding of the underlying phenomena which actuated intellectual developments in the past and which are still relevant to today’s knowledge-making processes. Howard Carlton received his PhD from the University of Birmingham, UK. His research explores a number of nineteenth-century astronomical controversies in order to demonstrate that the ideas of participants in these debates were materially altered by traumatic life-events, as evidenced by their subsequent productions and their performances of altered selves.